INTEGRATING TECHNOLOGY IN ACCOUNTANCY: UPSKILLING, UNDERSKILLING AND RESKILLING - Bajada, Kisha Anne; Buriel, Andrea B; Geroch, Ma Nicole; Villaruz, Monecita A (President University, 2024)
The aim of this research is to address the integration of technology in terms of upskilling, reskilling, and under-skilling among accountancy students of Colegio de la Purisima Concepcion. The study’s dilemma emerged from concerns involving the student’s competence and existing skill set when faced with technology modernization. To gather information on the current condition of the problems under consideration, the study used a descriptive and correlational research approaches utilizing a validated and pilot-tested survey questionnaire to a randomly selected 175 accountancy students. The major findings show that students perceive reskilling as a necessity alongside under-skilling and upskilling in order to navigate the technology advancements in the evolving industry. Additionally few approaches are also highlighted such as participation on professional development activities and investment on technology. Overall, the research determined that while accountancy students of Colegio de la Purisima Concepcion have basic technology integration skills, there is still room for improvement, notably on utilizing advanced software and platform, the availability of equipment and instructor. The study provides insights into the hindrance that accountancy students confront, while giving the institution the idea of current curriculum modifications to give students the competitive advantage in the job market and equipping them with necessary skills to strive in the industry.